Cutaneous melanomas attributable to ultraviolet radiation exposure by state. Issue 5 (17th February 2020) - Islami, Farhad; Sauer, Ann Goding; Miller, Kimberly D.; Fedewa, Stacey A.; Minihan, Adair K.; Geller, Alan C.; Lichtenfeld, J. Leonard; Jemal, Ahmedin
Abstract : Information on cutaneous melanoma (melanoma) burden attributable to ultraviolet (UV) radiation by state could inform state and local public health policies to mitigate the burden. We estimated numbers, proportions and age‐standardized incidence rates of malignant melanomas attributable to UV radiation in each US state by calculating the difference between observed melanomas during 2011–2015 and expected cases based on historically low incidence rates among whites in Connecticut from 1942 to 1954. The low melanoma burden in Connecticut during this period likely reflected UV exposure accumulated in the 1930s or earlier, when exposure was likely minimized by clothing style and limited recreational exposure. The estimated number of melanoma cases attributable to UV exposure during 2011–2015 in the United States was 338, 701, or 91.0% of the total cases (372, 335); 94.3% (319, 412) of UV‐attributable cases occurred in non‐Hispanic whites. By state, the attributable proportion among non‐Hispanic whites ranged from 87.6% in the District of Columbia to 97.3% in Hawaii. The attributable age‐standardized rate (per 100, 000) among non‐Hispanic whites ranged from 15.1 (95% CI, 13.4–16.7) in Alaska to 65.1 (95% CI, 61.4–68.9) in Hawaii and was ≥23.3 in half of states. Considerable proportions and incidence rates of melanoma attributable to UV radiation in all states underscores the need for broad implementation or enforcement of preventive measures across states, with priority for states with higher burden. Abstract : What's new? In the United States, the vast majority of melanomas are attributable to ultraviolet (UV) radiation. Little is known, however, about the state‐by‐state burden of melanoma due to UV exposure. This study shows that UV‐attributable melanoma incidence rates among non‐Hispanic whites vary substantially among U.S. states. Relative to historical reference data, for the period 2011‐2015 the proportion of UV‐attributable melanomas ranged from 87 to 97.3 percent, while cases ranged from 15.1 to 65.1 per 100, 000 persons. Despite these variations, the relatively high burden of UV‐attributable melanoma in each state highlights the need for prevention strategies that reach the entire U.S. population.